Para sport and anti-doping: a study of Swedish Para athletes' experiences and perceptions - Qvarfordt, Anna; Svedsäter, Göran; Fagher, Kristina; Bjerkefors, Anna; Blomqvist, Sven (Frontiers in Sports and Active Living, 2024)
Introduction A well-functioning anti-doping system relies on being perceived by athletes as effective, fair, and practically feasible to implement. While research has highlighted the views of Olympic athletes on anti-doping over the past decade, the experiences and perceptions of Para athletes have not been extensively explored. The purpose of this study was to examine Swedish elite Para athletes' experiences and perceptions of the policy and practice of the anti-doping system. Methods A quantitative cross-sectional approach was used, with a web survey elaborated from a survey with Olympic athletes adjusted for Para athletes with physical, visual, and intellectual impairments. The sample consisted of 66 active Para athletes competing at national or international level (response rate 71%). Data were analyzed using descriptive statistics and differences between subgroups were examined Fisher's exact test. Thematic analysis was employed to analyze open-ended questions. Results Most of the respondents expressed a positive outlook on the anti-doping system, advocating for comprehensive efforts. A significant portion (35%) had not received anti-doping education, with those who did reporting increased confidence in avoiding unintentional doping. Despite their elite status, half of the respondents had not undergone doping control. Mistrust regarding the system's effectiveness and fairness was identified, with over half of the participants emphasizing the need for new technical solutions to enhance procedures specifically tailored for Para athletes. Discussion The athletes in this study advocate for a Para sports-focused approach in the anti-doping system, emphasizing equal testing opportunities, procedural adjustments for independence and privacy, and increased access to education. The findings illuminate the unique conditions faced by athletes with impairments within the anti-doping system, offering valuable insights for policymaking in the development of anti-doping strategies tailored to Para athletes and their various impairments.